In Vivo Investigation of Soft Tissue Response of Novel Silver/Poly(Vinyl Alcohol)/ Graphene and Silver/Poly(Vinyl Alcohol)/Chitosan/Graphene Hydrogels Aimed for Medical Applications – The First Experience - Lužajić Božinovski Tijana1 (Sciendo, 2018)
In this paper, we have shown for the fi rst time the soft tissue response of novel silver/ poly(vinyl alcohol)/graphene (Ag/PVA/Gr) and silver/poly(vinyl alcohol)/chitosan/ graphene (Ag/PVA/CHI/Gr) nanocomposite hydrogels aimed for medical applications. These novel hydrogels were produced by in situ electrochemical synthesis of silver nanoparticles in the polymer matrices as described in our previously published works. Both Ag/PVA/Gr and Ag/PVA/CHI/Gr, as well as controls Ag/PVA, Ag/PVA/CHI and commercial Suprasorb©hydrogel discs, were implanted in the subcutaneous tissue of rats. Implants with the surrounding tissue were dissected after post-implantation on days 7, 15, 30 and 60, and then processed for histological examination. The tissue irritation index (TIrI) score, according to ISO 10993-6, 2007, as well as the number of leukocytes in the peri-implant zone and connective tissue capsule thickness were examined. The results show that each TIrI score, the leukocyte number around the implanted materials and capsule thickness gradually decreased during the observation period. At the endpoint of follow-up, the Ag/PVA/CHI/Gr implant was surrounded with a thinner capsule, while both the TIrI score and the number of leukocytes of the peri-implant zone were greater compared to the Ag/PVA/Gr implant. Despite the observed differences, we can conclude that our in vivo experiment suggested that both novel hydrogels were biocompatible and suitable for medical use.